Apical Periodontitis in Root-Filled Teeth Endodontic Retreatment and Alternative Approaches (Springer International Publishing, 2018)
This book is a comprehensive guide to apical periodontitis in root-filled teeth that covers not only all aspects of diagnosis and management but also epidemiology, etiology, consequences, clinical decision-making, and prognosis. There is a particular focus on the available surgical and nonsurgical methods of retreatment designed to restore healthy periapical conditions. Alternatives to retreatment are also explored, including a conservative approach involving monitoring of the diseased tooth without intervention and the option of extraction and replacement with an implant or a fixed prosthesis. The goal of root canal treatment is to save the natural tooth even when tissue breakdown has resulted in pathological conditions of the pulp and periradicular tissue. However, population studies reveal that complete healing is often absent in root-filled teeth, and apical periodontitis is frequently observed in conjunction with root fillings of poor technical quality. Under these circumstances, questions arise as to how the apical periodontitis is impacting on the patient and how the condition should be tackled. Readers will find this well-illustrated book to be of great value in directing clinical practice.